Phage therapy: going temperate? - Monteiro, Rodrigo (2019)
Strictly lytic phages have been consensually preferred for phage therapy purposes. In contrast, temperate phages have been avoided due to an inherent capacity to mediate transfer of genes between bacteria by specialized transduction â an event that may increase bacterial virulence, for example, by promoting antibiotic resistance. Now, advances in sequencing technologies and synthetic biology are providing new opportunities to explore the use of temperate phages for therapy against bacterial infections. By doing so we can considerably expand our armamentarium against the escalating threat of antibiotic-resistant bacteria.